Bovidae (Mammalia) from the early Middle Miocene of Maboko, Kenya - (:unkn) unknown (My University, 2023)
We describe here the Bovidae from the early Middle Miocene site of Maboko, Kenya, known for its rich and highly diverse assemblage of Primates. They are attributed to two taxa of slightly different sizes, Turcocerus africanus n.sp. and Kubanotragus pickfordi. In addition to Kenya, Turcocerus ranges through the Middle Miocene from Turkey to China; it might have originated in Africa but the lack of precise dating weakens any phylogeographic hypothesis. Kubanotragus has similar chronological and geographic ranges. Both Maboko species retain primitively low levels of hypsodonty compared to their northern relatives and may have been less specialized for grazing than Eurasian taxa. The Maboko Bovidae illustrate an early diversification of the family in Africa that appears to pre-date the major diversification of Bovidae and appearance of the diverse clades that are characteristic of modern African pecoran faunas.
Keywords: African Research